Long-chain n-3 PUFA in vegetarian women: a metabolic perspective - Graham C. Burdge; Sze-Yen Tan; Christiani Jeyakumar Henry (Journal of Nutritional Science, 2017)
Vegetarian diets have been associated with health benefits, but paradoxically are low in EPA and DHA which are important for development, particularly of the central nervous system, and for health. Humans have limited capacity for synthesis of EPA and DHA from α-linolenic acid, although this is greater in women than men. Oily fish and, to a lesser extent, dairy foods and meat are the primary sources of EPA and DHA in the diet. Exclusion of these foods from the diet by vegetarians is associated consistently with lower EPA and DHA status in vegetarian women compared with omnivores. The purpose of the present review was to assess the impact of low EPA and DHA status in vegetarian pregnancies on the development and health of children. EPA and DHA status was lower in breast milk and in infants of vegetarian mothers than those born to omnivore mothers, which suggests that in the absence of pre-formed dietary EPA and DHA, synthesis from α-linolenic acid is an important process in determining maternal EPA and DHA status in pregnancy. However, there have been no studies that have investigated the effect of low maternal DHA status in vegetarians on cognitive function in children. It is important to address this gap in knowledge in order to be confident that vegetarian and vegan diets during pregnancy are safe in the context of child development.